Relative improvements in road mobility as compared to improvements in road accessibility and economic growth: a cross-country analysis - Choy, Peng Ng; Law, Teik Hua; Wong, Shaw Voon; Subramanian, Kulanthayan (Elsevier, 2017)
Previous studies indicated that an increase in road length had a positive and statistically significant impact on economic growth. However, the demand for and development of highly mobile or highly accessible roads likely varies according to the level of economic development, and this might have a significant influence on economic growth. The objectives of the present study were twofold: 1) to evaluate how road infrastructure growth facilitates export-led growth processes and 2) to determine the investment level needed for different road types to facilitate economic and commercial activities at different developmental levels. To shed light on these issues, fixed-effects linear regression analysis was conducted using time-series cross-sectional data on the relative improvement in road mobility as compared to improvement in road accessibility (MPA) and economic growth for 60 countries over the period 1980–2010. The key finding of this study was that in countries with a medium and high level of development, improvements in road mobility facilitated export-led growth. This indicates that policies to promote export should be implemented in conjunction with high-mobility road network expansion to enhance economic growth, particularly in countries with a medium level of development, which generally suffer from lower levels of high-mobility road network development. Such expansion in road mobility is necessary to fulfill demands for long-distance travel and enable the transportation of goods and services across regions, thereby facilitating productivity and trade. On the other hand, in countries with a low level of development, more investment is required to build roads with higher accessibility. Such roads are required to facilitate local business and trade activities. This type of road development is necessary to achieve sustainable economic growth in these countries.